The impact of the Meals‐to‐You program on food insecurity. Issue 3 (21st June 2022) - Anderson, Theresa; Waxman, Elaine; Gundersen, Craig
Abstract: Food insecurity among children in the United States remains a serious problem, especially during summer months. While there are summer meal programs such as the Summer Food Service Program (SFSP), participation rates are low. In response, in 2019, Meals‐to‐You (MTY) was piloted by the U.S. Department of Agriculture through the Baylor Collaborative on Hunger and Poverty where food boxes were delivered to households with a focus on rural areas. This was expanded during COVID to an Emergency Meals‐to‐You component. We find that among participating households, those receiving more boxes had larger declines in food insecurity, especially in more remote rural areas.